Sociological Analysis of the Iran Social Science Elites Opinion about Socio-Economic Development - Mahmood Bastaminezhad; Akbar Talebpour; Khalil Mirzaei (توسعه اجتماعی)
The aim of this study was to achieve a theoretical consensus of the view of Iranian social scientists on socio-economic development. According to the research objectives, the qualitative approach and Delphi research method have been used. The participants of this research included all those who were in the field of development and had a book, article or research effect. Using a targeted sampling method, 15 of these people were selected as contributors. Kendall coordination coefficient was used to determin the degree of consensus among Delphi panel members and 70 percent was set as level of consensus. The results indicated that if we consider the government as a combination of the three parts of the government , judiciary and the people if they use a good governance strategy they will interact with each other and government with meritocracy , reducting the share of oil in the country’s budget , reform of administrative and tax system and establish key financial institutions such as an independent central bank and strong budget management on the other hand and judiciary by establishing the role of law, controlling corruption and improving transparency indicators in the country on the other hand , creates the environment and security for the market to create production, employment and economic prosperity. Meanwhile the participation of the people in the government has led to the realization of civil society, including a free press, parties and independent media, which act as a bridge between government and society and provide the basis for further monitoring of the performance of government and officials and their accountability. The combination and interaction of these parts together pave the way for achieving the goals of this strategy that’s mean: providing basic services, realization of social justice, strengthen democratic structures, extending the social security umbrella , improving the quality of the environment , increase productivity and, … to provide. In such a context, it will be easier to achieve socio-economic development.